(untitled) (Acta Entomologica Serbica, 2021)
Herein we present the first record of a very rare species of parasitoid wasp, Mantibaria seefelderiana, in Croatia, with the basic elements of its unusual biology. The most precise categorization of its trophic interaction would be pseudoparasitoid, because the larva of this species feeds on a larger number of mantis embryos in the ootheca in a way that is more representative of predatory diet and behavior, without any regulation by its host’s behavior. Additionally, adult females of this pseudoparasitoid live as ectoparasites attached to the body of female mantises, where they feed on hemolymph. The combination of an unusual predatory and parasitic lifestyle is extremely atypical for the predominantly parasitoid character of most other members of the family Scelionidae.